Victim Sensitivity and Proposal Size Modulate the Ingroup Favoritism During Fairness Norm Enforcement - Zhang, Zhen; Zhao, Hui; Liu, Ruixue; Qi, Chunhui (Frontiers in Psychology, 2021)
People show a strong aversion to inequality, and are willing to sacrifice own interests to punish violations of fairness norms. Empirical research has found that group membership could influence individuals’ fairness judgement and norm enforcement, but has shown inconsistent findings and has not focused much on the potential moderators. Here two studies aim to investigate whether victim sensitivity and proposal size moderate the impact of group membership on reactions to unfair proposals. In both studies, participants with different victim sensitivity (low vs. high group) played the hypothetical (Study 1) and incentivized (Study 2) ultimatum game under the intragroup and intergroup condition, and indicated their responses to different proposals. Results showed that, regardless of victim sensitivity, ingroup member is often given preferential and positive treatment. Low victim sensitive persons are more likely to accept unfair offers from ingroup than outgroup, while this effect was attenuated for these with high victim sensitivity, especially for highly ambiguous unfair offers (offer 6:4 in Study 1 and offer 8:2 in Study 2). Moreover, the ingroup favoritism score for ambiguous unfair offers was smaller for high compared to victim sensitivity group. Taken together, victim sensitivity and proposal size could moderate the ingroup favoritism on responses to unfairness.